What violations of international human rights law did Russia commit during its annexation of the Crimea and what remedies are available for the victims? (International Journal of Scientific Research and Management (IJSRM), 2018)
Today the world is still in shock, after the unprecedented decision of President Putin to annex the Crimea territory. Was it Russia’s attempt to awaken its neo-imperialism or a simple case of assertion of national sovereignty? The question posed to the people was now weather a new road to the European Union and the West, or a pursuit of the historic ties with Russia was the right answer? Furthermore, this paper examines the arguments put forward by the alienated Russian doctrine of International Law. I argue, that Russia’s annexation of Crimea was a violation on a range of complex and intricate principles of International Law which serves to guarantee Ukraine’s territorial integrity and security. In the course of this paper it will become apparent that the arguments made by Russia are indefensible, and are in stark contrast to previous Russian doctrinal approaches in terms of self-determination and territorial integrity. This paper will attempt to provide reason- able evidence to support its claim that Russia had no right to interfere within Ukraine’s territorial integrity nor to facilitate actions against it.